Neurofibromatosis type 1 (Von Recklinghausen´s disease) in Emergency Department - Ly-Pen, Domingo; Ly Liu, Diana (International Journal of Innovative Research in Medical Science, 2016)
Neurofibromatosis is one of the most common genetic disorders. A typical picture is presented, with a brief compilation of the most common presentations of these patients in the Emergency Department.